Соціально-економічний стан Півдня України у 60-х роках ХХ ст. (історіографія проблеми) - Шарін, О.В. (Історичний архів. Наукові студії, 2014)
Розкрито стан вивчення проблеми соціально-економічного стану Півдня України у 60-х
роках ХХ ст. Охарактеризовано наукові розвідки минулих років та сучасності. Подано
огляд наукової літератури з досліджуваної теми відповідно до проблемно-хронологічного
принципу історіографії. Відповідно до авторських концепцій розуміння соціально-
економічних реформ зазначеного періоду, розкрито найважливіші досягнення та
прорахунки здійснених перетворень. Дана оцінка ступеню висвітлення поданої теми. Раскрыто состояние проблемы социально-экономического положения Юга Украины
в 60-х годах ХХ в. Охарактеризовано научные исследования прошлых лет и совре-
менности. Дан обзор научной литературы по исследуемой тематике в соответствии с
проблемно-хронологическим принципом историографии. Согласно авторским концепциям
понимания социально-экономических реформ указанного периода, раскрыто важнейшие
достижения и просчеты осуществленных преобразований. Дана оценка степени
освещения данной темы. The scientific reconstruction of the history of the Ukrainian people is an important
prerequisite for its full national-spiritual life. An objective analysis of historical experience
contributes to the solution of modern problems, determination of the dominant social orientation
further development.
The past of the southern region of Ukraine is behind a particular scientific interest. The
historical development of the South during the Soviet period is not adequately covered in the
literature, which poses a problem its comprehensive analysis to national historical science. The
proposed work is an attempt to analyze and systematize the works of scientists regarding to
socio-economic situation of the Southern Ukraine in the 60`s of the twentieth century, during the
so-called "The Khrushchev thaw" and reforms in the middle of the 60`s.
The modern socio-economic situation in Ukraine adds the relevance to the subject especially
in the context of economic reforms, which will have to start work in the nearest future. The
analysis of historical experience of social and economic construction, namely a period of rapid
rise of productive forces and improvement of social area enables an opportunity to the most
pragmatically and reasonably carrying out the socio-economic reforms in modern Ukraine.
Therefore the history of socio-economic changes in the 60`s of the twentieth century this is the
two waves of reforms are important for making modern concepts of development. Because the
global economic crisis poses a real challenges before Ukrainian people and the ability to
compete in a global world. As a result of this, in the opinion of the author, appeal to own
historical experience can help overcome the crisis in modern Ukraine.
The review of scientific literature of the investigated subject realized according to problemchronological
concept of historiography.
Based on comprehension of national and foreign historiography investigated the socioeconomic
state of the south of Ukraine during the period of reforms in the 60`s of the twentieth
century. They were an attempt of improving the Soviet totalitarian system. The article highlights
the specificity of region`s development during the indicated period. It based on the analysis of
little known and previously not used archival documents and published sources.